Killing in the name of …? Ethnic group identities and civil war - Rørbæk, Lasse Lykke (Politica, 2016)
The article discusses two competing understandings of the relationship between ethnic group identities and civil war. The first one stresses the differences between ethnic group identities and proposes that religious and racial boundaries are particularly conflict-prone. According to the other understanding, ethnic groups generally have dense social networks, and their incentives and opportunities for fighting are associated with their political status and resources rather than their specific identity types. The article finds no statistical evidence that the probability of civil war onset is affected by whether ethnic groups primarily are mobilized around religious, linguistic, racial, or regional boundaries. The analysis thus suggests that different ethnic group identities are alike in terms of conflict escalation.